Preclinical safety studies of medicines in the Eurasian economic union - G. N. Engalycheva; R. D. Syubaev; A. D. Durnev (Фармакокинетика и Фармакодинамика, 2025)
This article analyzes the regulatory, scientific, and methodological documents of the Eurasian Economic Union (EAEU) and the Russian Federation devoted to conducting preclinical studies on the safety of medicines. Areas for which it is advisable to develop special EAEU guidelines for conducting preclinical safety studies have been identified. Based on an analysis of the international regulatory and methodological framework, elements of foreign experience in preclinical assessment of the safety of medicines for transfer to the practice of the Union are proposed.